2016
DOI: 10.1161/jaha.116.003868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Abrogation of Adenosine A 3 Receptor Prevents Uninephrectomy and High Salt–Induced Hypertension

Abstract: BackgroundEarly‐life reduction in nephron number (uninephrectomy [UNX]) and chronic high salt (HS) intake increase the risk of hypertension and chronic kidney disease. Adenosine signaling via its different receptors has been implicated in modulating renal, cardiovascular, and metabolic functions as well as inflammatory processes; however, the specific role of the A3 receptor in cardiovascular diseases is not clear. In this study, gene‐modified mice were used to investigate the hypothesis that lack of A3 signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…Likewise, there is evidence that both A 2A and A 2B receptors regulate fibroblast function, including cardiac fibroblasts, although there are conflicting reports on their specific effects (Zhong et al, 2005 ; Villarreal et al, 2009 ; Zhang et al, 2014 ; Karmouty-Quintana et al, 2015 ; Shaikh and Cronstein, 2016 ). These observations and reports of adenosine receptor involvement in various chronic diseases (Long et al, 2010 ; Wang et al, 2010 ; Bot et al, 2012 ; Koupenova et al, 2012 ; Sangsiri et al, 2013 ; Zhang et al, 2013 ; Teng et al, 2014 ; Nayak et al, 2015 ; Yang et al, 2016 ), clearly warrant more studies on adenosine receptor modulation of chronic myocardial ischemia.…”
Section: Chronic Myocardial Ischemia Modelsmentioning
confidence: 72%
See 1 more Smart Citation
“…Likewise, there is evidence that both A 2A and A 2B receptors regulate fibroblast function, including cardiac fibroblasts, although there are conflicting reports on their specific effects (Zhong et al, 2005 ; Villarreal et al, 2009 ; Zhang et al, 2014 ; Karmouty-Quintana et al, 2015 ; Shaikh and Cronstein, 2016 ). These observations and reports of adenosine receptor involvement in various chronic diseases (Long et al, 2010 ; Wang et al, 2010 ; Bot et al, 2012 ; Koupenova et al, 2012 ; Sangsiri et al, 2013 ; Zhang et al, 2013 ; Teng et al, 2014 ; Nayak et al, 2015 ; Yang et al, 2016 ), clearly warrant more studies on adenosine receptor modulation of chronic myocardial ischemia.…”
Section: Chronic Myocardial Ischemia Modelsmentioning
confidence: 72%
“…In contrast cardioprotective interventions in humans occur in the presence of various co-morbidities, such as arterial hypertension, obesity, diabetes, hypercholesterolemia, and often advanced age. Although there are numerous reports examining the role of adenosine and its receptors in these pathologies (Long et al, 2010 ; Wang et al, 2010 ; Bot et al, 2012 ; Koupenova et al, 2012 ; Sangsiri et al, 2013 ; Zhang et al, 2013 ; Teng et al, 2014 ; Nayak et al, 2015 ; Yang et al, 2016 ), the only one of these areas in which adenosine cardioprotection has been examined is in healthy aged rats and mice, and results have been conflicting. Isolated heart studies in 16–18 month old mice indicate a loss in the ability of adenosine and the A 1 and A 3 adenosine receptor agonists CPA and Cl-IB-MECA to reduce ischemia-reperfusion injury (Headrick et al, 2003 ; Peart et al, 2014 ).…”
Section: Lack Of Clinically Relevant Animal Modelsmentioning
confidence: 99%
“…In addition, more recently, it has been demonstrated that A 2B receptor blockade in hypoxia significantly decreased renal fibroblast proliferation and activation with a consequent reduction of profibrotic cytokine release, thus preventing the generation and development of renal fibrosis, the outcome of all types of chronic kidney disease (Tang et al , ). Indeed, in a novel mouse model of renal and cardiovascular disease induced through uninephrectomy and chronic high salt intake, the inhibition of A 3 receptor signalling prevented the development of hypertension and attenuated the cardiac hypertrophy and fibrosis together with renal injuries and proteinuria (Yang et al , ) (Figure ). This finding accords with that of a previously reported study showing that A 3 receptor antagonism reduces the progression of renal fibrosis (Lee et al , ).…”
Section: Pathological Role Of Adenosine In Inflammatory Conditionsmentioning
confidence: 99%
“…But inhibition of the receptor with MRS1523 had no significant effect on modulating lipolysis, at least in murine BA ( Gnad et al, 2014 ). However, the A 3 R KO mice had less abdominal and total body fat, and mice were protected from hypertension and cardiovascular diseases in the chronic kidney disease model tested ( Yang et al, 2016 ).…”
Section: Adenosine Receptors In Adipose Tissuementioning
confidence: 99%